Registries as useful tools in characterization of allergic manifestations. Issue 3 (June 2016) - Jares, Edgardo José; Badellino, Héctor Ariel; Ensina, Luis Felipe
Abstract : Purpose of review: Registries are useful to discover the applicability of data generated from randomized clinical trials (RCTs) into daily practice, and to search for real-life data usually not covered by them. Recent findings: In allergy, registry research brought clues to important epidemiological and clinical problems hardly accessible with other methods. The increase in the asthma prevalence in Sweden in contrast with stabilization in Denmark; the association of the prevalence of asthma and environmental factors; the knowledge of existing rhinitis international guidelines, but the poorly complacence of some of their recommendations; the low epinephrine use in anaphylaxis and the difference among European and Latin American elicitors; the predominance of β lactams or NSAIDs as drug hypersensitivity reactions inducers in different regions; the fact that most of the hereditary angioedema patients were receiving long-term prophylaxis with attenuated androgens; all the mentioned are clear examples of relevant and important data provided by current registries. Summary: Registries in allergy enlighten knowledge in areas not covered by classical investigational methods. As the number and importance of registries is growing, its contribution to the knowledge and management of allergic diseases will increase in the near future.